2013
DOI: 10.1080/07370024.2013.823823
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to This Special Issue on Transnational HCI

Abstract: It is not surprising that HCI researchers are attracted to the role of technology in global processes as many of us already live inherently transnational lives. While the notion of global connectedness is hardly new, the issues that confront us are more than specific concerns for remote migration, distributed work, or developing nations. Rather, we argue that transnational HCI is a contemporary condition of the design and use of technological systems, both at home and abroad. This special issue of HumanCompute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…The theme of culture, migration and technology, however, is set to grow and intensify. As recent studies have shown, cross-cultural and transnational issues in technology use are gaining in prominence [9,10,32,35]. In some ways, it may be reassuring that users around the globe are not heading straight for a uniform, homogenous global village.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…The theme of culture, migration and technology, however, is set to grow and intensify. As recent studies have shown, cross-cultural and transnational issues in technology use are gaining in prominence [9,10,32,35]. In some ways, it may be reassuring that users around the globe are not heading straight for a uniform, homogenous global village.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Depending on the intercultural context, users may have to use more than one particular SNS and maintain several online presences in order to stay in touch with back home and to embrace a new social environment. The management of such hybrid communities has recently been identified as one of the main challenges in a transnational perspective on Human-Computer Interaction [9], and early evidence suggests that users are sensitive to the cultural context suggested by a particular SNS [10,32]. We extend this perspective by proposing that alternating SNS use may be a necessity as well as a given for migrants.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Translocality as analytical lens is based within the research on transnational approaches for HCI. Transnational HCI is a research agenda, which seeks to emphasize certain aspects of the globalized world and the contemporary conditions by which ICT enables and constrains people's practices in ways fundamental to design and use of technologies (Shklovski, Vertesi et al 2014). Transnational HCI research provides a vocabulary and an agenda, which place studies of 'the global' in new ways, by rephrasing certain key concepts, as well as replacing commonly held perspectives and challenging basic assumptions about the impact of ICT in a globalized world.…”
Section: Translocalitymentioning
confidence: 99%
“…It provides us with a new analytical frame, which can help us re-think the ways in which we approach our investigations of global work. The first shift in our analytical understanding is the shift that replaces the dichotomy of global/local with the concept of translocal (Shklovski, Vertesi et al 2014). The issue with the global/local dichotomy is that it assumes that, we can distinguish between what is local and what is global, while in reality cultural practice will always be experienced from a certain perspective, thus the global is experienced and enacted through the local circumstances.…”
Section: Translocalitymentioning
confidence: 99%